Bacterial Hen1 is a 3′ terminal RNA ribose 2′-O-methyltransferase component of a bacterial RNA repair cassette - Jain, Ruchi (Cold Spring Harbor Laboratory Press, 2010)
Hen1 is an RNA ribose 2′-O-methyltransferase that modifies the 3′ terminal nucleoside of eukaryal small regulatory RNAs. Here, we report that Hen1 homologs are present in bacterial proteomes from eight different phyla. Bacterial Hen1 is encoded by the proximal ORF of a two-gene operon that also encodes polynucleotide kinase-phosphatase (Pnkp), an RNA repair enzyme. Purified recombinant Clostridium thermocellum Hen1 is a homodimer of a 465-amino acid polypeptide. CthHen1 catalyzes methyl transfer from AdoMet to the 3′ terminal nucleoside of an RNA oligonucleotide, but is unreactive with a synonymous DNA oligonucleotide or an RNA with a single 3′-terminal deoxyribose sugar. CthHen1 is optimally active at alkaline pH and dependent on manganese. Activity is inhibited by AdoHcy and abolished by mutations D291A and D316A in the putative AdoMet-binding pocket. The C-terminal fragment, Hen1-(259–465), comprises an autonomous monomeric methyltransferase domain.